Cytodiagnosis and histopathology necks amputees in genital prolapse operations - Herrera Calmet, Abelardo (2015)
609 sick or is the 27,89% of ginecópatas interned from 1955 to 1959 in our department were carrying PG 554 (90.96%) underwent surgery and 251 of these high amputation were asked neck as a time in the treatment of PG The highest incidence of amputations fall on the PG 111 gr. (53%). The most common age at which amputated neck is between 40-60 years (54%). The operation was carried Manchester operation with 233 cases (93%). The cytodiagnosis was negative in 233 sick in one doubtful and 17 not done them. Histopathological result of the collars was 249 amputees chronic cervicitis and colon cancer, one in situ and one infiltrating, which gives us a 0.86% false negative cytodiagnoses. We believe that these results were due to poor technique in making smear, to insufficient sample or the depth of the cancerous lesion. We are convinced that the cytodiagnosis is a valuable method in the screenings and must be confirmed by biopsy or tapering neck in cases of positive or equivocal results.